Relationship Between Knowledge of Giving Warm Water Compresses to Prevent Breast Milk Retention in Postpartum Mothers - Br Ginting Munthe, Novita; Sembiring, Iskandar Markus (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2024)
Breast milk dams are a common problem often experienced by postpartum mothers, which if not treated properly can cause pain, infection and obstacles in the breastfeeding process. One method that is known to be effective in preventing breast milk dams is by applying warm water compresses. This study aims to analyze the relationship between the level of knowledge of postpartum mothers regarding giving warm water compresses and preventing breast milk dams. This study used a cross-sectional design involving 60 postpartum mothers at the Juliana Clinic, Deli Serdang Regency, North Sumatra, Indonesia. Data was collected through a questionnaire that measured the mother's level of knowledge about warm water compresses and the incidence of breast milk dams. The results showed that the majority of mothers had sufficient (41.7%) and good (33.3%) knowledge about warm water compresses, while 25% of mothers had insufficient knowledge. As many as 58.3% of mothers did not experience breast milk dams, while the other 41.7% experienced breast milk dams. The results of the chi-square test showed that there was a significant relationship between postpartum mothers' knowledge about warm water compresses and prevention of breast milk dams (p-value < 0.05). Mothers with good knowledge experience breast milk dams less often than mothers who have less knowledge. In conclusion, good knowledge about warm water compresses has proven effective in preventing breast milk dams. More intensive education and counseling for postpartum mothers is needed to increase their knowledge about appropriate breast care techniques to prevent lactation problems.